Analyzing the Phenomenon: Exploring the Popularity and Representation of Women in the Indonesian Soap Opera "Cinta Fitri" - Narang, Bernika Yustisiana (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
The soap opera "Cinta Fitri" is one of the most popular TV drama series (soap operas) not only in Indonesia but also in Singapore (MdEntertainment). This paper focuses on the phenomenon of soap operas and gender representation in Indonesian media. The research methods that will be used in this research include content analysis, case studies, surveys and statistical analysis, literature studies, and comparative analysis. The Indonesian soap opera "Cinta Fitri" captivates audiences with its portrayal of personal struggles and complex relationships. Lead characters Fitri and Farrel challenge traditional gender norms, resonating with viewers. The show's popularity is fueled by its relatable storyline, strong character dynamics, and dedicated fan base, making it a cultural phenomenon in Indonesia. "Cinta Fitri" is an Indonesian soap opera that was successful because it presented an evocative story, strong characters who challenged traditional gender norms, and received fanatical support from the audience. By focusing on personal conflicts and relationships between characters, this soap opera shows its appeal and becomes a cultural phenomenon that influences views on gender in Indonesia.